REKRUTMEN CALON ANGGOTA LEGISLATIF PEREMPUAN OLEH PARTAI POLITIK DI KOTA PEKANBARU PADA PEMILU 2009; KASUS PARTAI DEMOKRAT, PARTAI DEMOKRASI INDONESIA PERJUANGAN DAN PARTAI KEADILAN SEJAHTERA - ', Wazni (Universitas Riau, 2011)
This study describes that how women legislative candidates were recruited by political parties atPekanbaru City in General Election 2009. The Democratic Party, The Indonesian Democratic Party ?Struggle and The Prosperous Justice Party become cases study. Firstly, The Democratic Party usedinternal mechanism by local patronage type. On other hand, The Indonesia Democratic Party ? Struggleused internal mechanism by central patronage type. However, both are an ascriptive style recruitment. Inaddition, The Prosperous Justice Party used internal mechanism by local bureaucratic. But, this style isan achievement oriented recruitment. Finally, in according to Kingsley that political party can consider 7points for recruitment. Namely, social background, political socialization, initial political activity,apprenticenship, occupational variables, motivation dan selection.Key words: political recruitment, women legislative candidates and political party.